1999
DOI: 10.1136/pgmj.75.881.145
|View full text |Cite
|
Sign up to set email alerts
|

Transient ischaemic attacks related to carotid stenosis precipitated by straining, bending, and sneezing

Abstract: SummaryThree patients are described in whom one or more carotid territory transient ischaemic attacks (TIAs) were preceded by sneezing, straining, or bending over. It is argued that the mechanism involved dislodgment of embolic material from the site of carotid atheroma. This mechanism should be considered as an alternative to paradoxical embolism when TIAs are precipitated by such physiological manoeuvres. Furthermore, TIAs should be added to the list of medical hazards associated with such events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Like coughing, sneezing is a well-recognized but hardly common cause of syncope; the previously suggested mechanism of a neurally mediated situational syncope is transient venous obstruction due to increased intrathoracic pressure, which may contribute to cerebral hypoperfusion [ 15 ]. In fact, sneezing, as in the Valsalva manoeuvre, is associated with increased intrathoracic pressure, arterial pressure rising to 80–90 mmHg [ 1 ], and venous pressure as well. Furthermore, the rise in intrathoracic pressure is associated with a rise in intracranial pressure [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Like coughing, sneezing is a well-recognized but hardly common cause of syncope; the previously suggested mechanism of a neurally mediated situational syncope is transient venous obstruction due to increased intrathoracic pressure, which may contribute to cerebral hypoperfusion [ 15 ]. In fact, sneezing, as in the Valsalva manoeuvre, is associated with increased intrathoracic pressure, arterial pressure rising to 80–90 mmHg [ 1 ], and venous pressure as well. Furthermore, the rise in intrathoracic pressure is associated with a rise in intracranial pressure [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, sneezing, as in the Valsalva manoeuvre, is associated with increased intrathoracic pressure, arterial pressure rising to 80–90 mmHg [ 1 ], and venous pressure as well. Furthermore, the rise in intrathoracic pressure is associated with a rise in intracranial pressure [ 1 ]. Moreover, it has been confirmed that coughing diminishes phasic carotid blood velocity and reduces cerebral perfusion [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 10 cases of intracranial/neurological injury after sneezing which included pneumocephalus 38 (1), cerebral venous thrombosis 30,33 (2), vertebral TIA 35 (1), migraine trigger 29,36 (2), transient ischemic attack 32 (1), spinal epidural hematoma 34,37 (2), and upper cervical infarction 31 (1). Sixty percent of these cases were in male patients.…”
Section: Resultsmentioning
confidence: 99%